Vegetation structure of associated flora in Amorphophallus gigas Teijsm. & Binn. (Araceae) habitats, North Padang Lawas Regency, North Sumatra - Rambey, Ridahati; Rahmawaty; Rauf, Abdul; Nababan, Esther Sorta Mauli; Delvian; Aththorick, T Alief; Ismail, Mohd Hasmadi (Horizon e-Publishing Group, 2024)
Amorphophallus gigas, a native aroid species found in the tropical forests of Sumatra, Indonesia, lacks robust population data despite previous spatial distribution studies. While not officially protected, A. gigas is considered rare in field documentation and faces potential habitat loss due to its proximity to the popular corpse flower. This 2023 study conducted in Halongonan District, North Padang Lawas Regency, North Sumatra, Indonesia, aimed to gather information on the habitat characteristics and associated flora of A. gigas to guide land conservation initiatives. The research focused on a forested area within three villages: Bargot Topong Julu, Napa Lancat, and Pangirkiran, utilizing a purposive random sampling approach. Plots covering 1 ha each were selected based on Amorphophallus in the generative phase across various land covers. Ecological analysis and indices were derived from collected vegetation data. The survey unveiled varying numbers of generative and vegetative A. gigas individuals across the three study sites. The understorey community at each site exhibited different levels of association with A. gigas, with Selaginella willdenowii, Clidemia hirta, and Leersia virginica showing strong positive correlations. The floral community in A. gigas habitats displayed diverse species richness and diversity across different growth stages and locations. Findings suggest that altitude, slope, pH, light intensity, air temperature, and humidity may influence A. gigas abundance in distinct ways. This study offers valuable insights into the biological and ecological factors influencing the distribution and abundance of A. gigas populations, providing guidance for conservation and management efforts.